Türk bankacılık sektöründe sorunlu kredilerin varlık yönetim şirketlerince tasfiyesi, seçilmiş ülkeler ve Türkiye uygulaması - Selimler, Hüseyin (My University, 2006)
TÜRK BANKACILIK SEKTÖRÜNDE SORUNLU KREDİLERİN VARLIK YÖNETİM ŞİRKETLERİNCE TASFİYESİ, SEÇİLMİŞ ÜLKELER VE TÜRKİYE UYGULAMASI Özet : Sorunlu kredilerin tasfiyesinde varlık yönetim şirketi etkin kullanılan bir yöntemdir. Çeşitli ülkelerde merkezi ve merkezi olmayan varlık yönetim şirketleri kurulm uş ve bankacılık sektöründe önemli bir role sahip olmuştur. Türk bankacılık sektöründe de sorunlu krediler önemli tutar ve oranlara ulaşmış, hem bankacılık sektörünü hem de reel sektörü etkilemiştir. TMSF’nun alacak satış ihaleleri, İstanbul Yaklaşımı ve bankaların faaliyetleri sorunlu kredilerin çözümünde kullanılmış yöntemlerdir. Varlık yönetim şirketi yönetmeliği yürürlüğe girmiş, 5411 sayılı Bankalar Kanununda da yer almıştır. Ancak, bugüne kadar amaçlandığı şekilde varlık yönetim şirketi kurulamamıştır. Çalışmamızda ülke örmekleri olarak G.Kore (Kamco), Malezya (Danaharta), Tayland (FRA,TAMC) ve Endonezya (IBRA) incelenmiştir. Türk bankacılık sektöründe, 2006 yılı itibariyle sorunlu kredilerin toplam krediler içindeki payı %4,7 , aktif içindeki payı %2,4 ve toplam tutarı 7.496 milyon YTL’dir. Türkiye bankacılık sektöründe hem TMSF’nin %100 sahip olacağı hem de TMSF’nin ortak olarak yer alacağı varlık yönetim şirketleri ile ikili bir model önerilmektedir. Yeniden yapılandırma ile satışın birlikte yürütüleceği, mevcut sorunlu kredilerin çözümünün öncelikli olacağı,tüm bankaların sorunlu kredilerinin alınabileceği ancak çeşitli önceliklerin ve kriterlerin olabileceği, TMSF’nin %100 sahip olduğu varlık yönetim şirketinin faaliyet süresinin sınırsız, ortak olarak katıldığı varlık yönetim şirketinin sınırlı olacağı, bankaların tüm sorunlu kredilerinin alınacağı ancak önceliğin ticari krediler olacağı, faaliyetini durdurmuş firmaların kredi borçlarının satış, faaliyetine devam eden firmaların kredi borçlarının yeniden yapılandırılacağı bir model önerilmektedir. Varlık yönetim şirketinin faaliyetlerinin etkin ve verimli olması için; BDDK tarafından muhasebe sistemi oluşturulmalı, tapu kayıtları merkezileştirilmeli, TCMB Risk Bildirim Cetvellerinde varlık yönetim şirketlerine devredilen sorunlu krediler de yer almalı, denetime tabi olmalı, bilgiler halka açık olmalı, vergi resim ve harç istisnası olmalıdır. LIQUIDATION OF NON-PERFORMING LOANS IN TURKISH BANKING SECTOR THROUGH ASSET MANAGEMENT COMPANIES, SELECTED COUNTRIES AND TURKEY APPLICATIONS Banks, Banking Sector, Non-performing Loans, Bank Loans, Asset Management Company, Turkish Banking Sector

Asset Management Company (AMC) is a method used in the effective liquidation of non-performing loans. In various countries, centralised and decentralised asset management companies have been established and have played an important role in their respective banking sectors. Similarly, non-performing loans (NPL) have reached a high amount and also rates in Turkish Banking Sector and affected both banking sector and firms, especially in the crisis periods. Many methods including non-performing loans sales of SDIF, Istanbul Approach and the liquidity facilities of banks have been used for resolving of non-performing loans. Asset Management Company regulation entered into force in 2002, Bank Act No 5411 contains an article that regulates AMC. Yet, an asset management company that fulfils the expectations could not be established so far. This study also examines the experiences of some countries; namely S.Korea (Kamco), Malaysia (Danaharta), Thailand (FRA, TAMC) and Indonesia (IBRA). In the Turkish banking sector, as of 2006, ratio of non-performing loans in total loans is 4.7% ratio of non-performing loans to total asset is 2.4% and its total amount is 7.496 million YTL. We suggest a dual modal in which SDIF possess 100% portion of an asset management company and also be a partner to other ones. The features of the suggested model are as follows; restructuring and disposition of loans should be done together, disposition of present non-performing loans should be the primary objective, non-performing loans of all banks should be taken but some priorities and criterions must be determined, the activity period of AMC that the SDIF has 100% share must be unlimited where as the same period in AMC that SDIF acts as partner is limited, all non-performing loans of banks should be transferred and taken to AMC but corporate loans should have a priority as oppose to individual loans, the non performing loans of non-operating companies should be disposed of immediately, NPL of operating companies must be restructured and be later disposed of. Suggestions for the effective asset management company are as follows; Accounting system should be established by the Banking Regulation and Supervision Agency, property registrations should be centred, non-performing loans transferred to AMC should be observed by the Central Bank of the Republic of Turkey through Risk Declaration Scales, AMC’s should be examined by audits, transparent to public in terms of providing information and shall be exempt from all kinds of taxes, duties and charges.
Keywords: Bankalar ve Bankacılık_Türkiye; Krediler